Years of lost life expectancy in Argentina, 2001-2010 - González, Leandro (2012)
This article describes the evolution of mortality in Argentina after the 2001 socioeconomic crisis. Life tables are obtained from population projections and vital statistics records. It shows the progress of life expectancy at birth for each sex and the Years of Life Expectancy Lost method is applied to analyze the changes in mortality. Throughout the decade male population progressed more than the female in terms of life expectancy, although the male overmortality remains high. The socioeconomic crisis produced a slight decline in life expectancy in 2002 and quickly recovered until 2005. In 2006-08 life expectancy decreased, but in last years increased again. Years of life expectancy lost show that violent deaths produce the largest loss of male life expectancy, while in female population are tumors. Also there is an increase in mortality due to respiratory diseases.